Students’ Perceptions on the Use of Lecture and Presentation Method in an Online Learning - Mawarti, Diah Ayu; Dieni, Novita Al Ihyak; Wibisono, Wawan (Universitas Muhammadiyah Kalimantan Timur, 2024)
The use of lecture and group presentation method in the Islamic Religious Education (PAI) course in online learning at 17 Agustus 1945 Semarang University (Untag Semarang) in the first semester of academic year 2021-2022 has an impact on the students’ acceptance. It is studied using qualitative approach. From the result of interview which was then associated with the result of observations during the teaching and learning process and then compared it with the result of the questionnaire, it can be seen that the application of the lecture method through the explanation of the material from the lecturer make students easier to understand the material than having to learn themselves. 79.8% of students like the lecture method and only 52.9% of students choose group presentation method. They also do not understand the explanation of online group presentations from other students. Judging from 41.3% of students, the reason is because they cannot discuss the material face to face.